CRISPR-Cas Systems in Helicobacter Pylori: A Dual Role in Genome Stability and Pathogenesis - Ibrahim, Noora Hamid; Abdulhussien, Adeeb Abdulally; Faqr, Ayoob Murtadha Alshaikh; Mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2025)
Helicobacter pylori is a Gram-negative bacterium that colonizes the human stomach and is implicated in various gastrointestinal diseases, including gastritis, peptic ulcers, and gastric cancer. Recent studies have revealed the presence of CRISPR-Cas systems in H. pylori, which play a complex role beyond their well-known function in adaptive immunity against foreign genetic elements. This review explores the dual role of CRISPR-Cas systems in H. pylori, focusing on their contribution to both genome stability and pathogenesis. CRISPR-Cas systems act as bacterial immune defenses, targeting invading phages and plasmids to prevent genomic disruption. In H. pylori, these systems maintain genome integrity by limiting horizontal gene transfer, which is crucial given the bacterium’s high genetic variability. However, H. pylori’s CRISPR arrays and Cas proteins also influence the bacterium’s virulence and ability to persist in the hostile gastric environment. Emerging evidence suggests that CRISPR-Cas components modulate gene expression involved in adhesion, motility, and immune evasion, thereby enhancing colonization and pathogenicity. Moreover, the interplay between CRISPR-Cas-mediated genome surveillance and bacterial adaptability highlights a balance between protecting genome stability and promoting genetic diversity necessary for survival in the dynamic gastric niche. Understanding this dual functionality provides insights into H. pylori’s evolution and pathogenic mechanisms and identifies potential targets for novel therapeutic strategies.